Assessment of risk factors associated with multidrug-resistant organism infections among patients admitted in a tertiary hospital - a retrospective study - Alaa F. Alsehemi; Emad A. Alharbi; Buthainah B. Alammash; Alaa I. Alrais; Hossein M. Elbadawy; Yaser M. Alahmadi (Elsevier, 2023)
Background: Bacterial resistance has become a global health concern. To treat suspected multidrug resistant organisms (MDROs), physicians first use broad-spectrum antibiotics; however, this increases the chance of developing antimicrobial resistance. Thus, defining the risk factors for MDROs could aid in the selection of the ideal initial antimicrobial therapy and improve clinical outcomes. Objective: This study aimed to identify the common risk factors for MDRO infection among patients admitted to King Fahad Hospital (KFH) and to analyze the comorbidity factors associated with MDRO infections. Methods: This retrospective, observational, case-control study included adult patients ≥ 18 years old admitted to KFH between 1st of January to 31st of March 2021, with positive microbial culture. Pediatric patients, outpatients, or patients with only positive fungal cultures were excluded. Data were obtained from the KFH laboratory MDRO documenting database. Results: Two hundred and seventy patients were included in this study: 136 in the study group and 134 in the control group. Among patients, 167 (61.9 %) were males and 184 (68.1%) were 18 to 65 years old. The use of drugs such as cotrimoxazole, amikacin, and imipenem (OR = 4.331, C. I. of OR:1.728, 10.855, p = 0.002) were significantly associated with MDRO infections, whereas cefazolin was associated with a lower risk of MDRO infections (OR = 0.080, C.I. of OR:0.018, 0.347, p < 0.001). The intensive care unit showed higher odds of significant association with MDRO infections than those of the surgical unit (odds ratio [OR] = 8.717, 95% C.I. of OR: 3.040, 24.998, p < 0.001). Patients who previously consumed acid-suppressive medications showed higher odds of developing MDRO infections (OR = 5.333, C.I. of OR: 2.395, 11.877, p < 0.001). Conclusion: The most significant comorbidities were diabetes, hypertension, antibiotic use prior to hospitalization and the use of cotrimoxazole, amikacin and imipenem among other antibtiotics was mostly associated with MRDO infections. This study revealed an increasing trend of MDRO infections and a positive correlation with the incidence of strokes and mortality, which highlights the importance of understanding the risk factors for MDRO infections.